Prevalence of oral habits in homeless children under care of Yayasan Bahtera Bandung - Gildasya Gildasya; Eriska Riyanti; Syarief Hidayat (Dental Journal (Majalah Kedokteran Gigi), 2006)
Oral habits, comprising of thumb and lip sucking, lip and nail biting, tongue thrusting and mouth breathing are commonly caused by disturbance in mental development. These persistent habits may lead to disturbance in physical growth, causing disorders such as malocclusion. Homeless children are prone to this condition. The purpose of this descriptive research was to present the prevalence of oral habits in homeless children under care of Yayasan Bahtera Bandung, by survey technique. The sample consisted of 92 children collected by purposive sampling. This research was conducted through interviews and clinical examnations of the oral cavity to elucidate signs of oral habits. The result showed 50% of homeless children performed oral habits, consisting of 26 boys (55,32%) and 20 girls (44.44%). The prevalence of thumb sucking habit was 21.74%, lip sucking or biting was 17.37%, tongue thrusting was 4,35%, nail biting and mouth breathing tied at 3,26%. The research concluded that a part of homeless children had oral habits, with boys as slight majority, and thumb sucking was the most performed.